Distal antral gastropexy – A novel technique to prevent recurrence of giant hiatus hernia in selected cases – A cohort study. (March 2015) - Goh, Y.L.; Chu, V.; Tokala, A.; Shetty, V.D.; Ward, J.B.; Date, R.S.
Abstract: Introduction: The recurrence rate of giant hiatus hernias (GHH) following repair is high (30%) and increases with the hernia size and previous revision surgery. The mechanism of recurrence is poorly understood. Methods: This is a retrospective cohort study of all consecutive patients who underwent repair of giant hiatus hernia in a tertiary upper GI referral centre from November 2000 to November 2014. Patients who underwent redo surgery were identified and data on intra-operative findings and procedure performed at primary and redo surgery from their operation notes were collected. Results: A total of 81 patients underwent primary repair of GHH over the 14 year study period. 10 (12.3%) had symptomatic/radiological recurrence of which 4 were found to have the distal stomach herniating into the chest despite having an intact intra-abdominal wrap/gastropexy. To prevent migration of the distal stomach into the chest, distal gastropexy - fixing the antrum to the anterior abdominal wall, was added to 'conventional' gastropexy in 5 subsequent cases, in whom the antrum was in the chest preoperatively. These cases have no evidence of recurrence at the end of 6 months follow up. Conclusion: Securing the antrum of stomach to the anterior abdominal wall may prevent migration of the distal stomach and other infracolic organs into the chest and thus reduce recurrence of some GHH where antrum had been in chest previously. Highlights: Recurrences after giant hiatus hernia occur through a defect anterior to the oesophagus. New pattern of recurrence of distal stomach herniating posterior to the oesophagus. This is prevented by performing additional gastropexy between antrum and anterior abdominal wall.